SMAD4 loss is associated with response to neoadjuvant chemotherapy plus hydroxychloroquine in patients with pancreatic adenocarcinoma. Issue 5 (18th May 2021) - Fei, Naomi; Wen, Sijin; Ramanathan, Rajesh; Hogg, Melissa E.; Zureikat, Amer H.; Lotze, Michael T.; Bahary, Nathan; Singhi, Aatur D.; Zeh, Herbert J.; Boone, Brian A.
Abstract: SMAD4, a tumor suppressor gene, is lost in up to 60%–90% of pancreatic adenocarcinomas (PDAs). Loss of SMAD4 allows tumor progression by upregulating autophagy, a cell survival mechanism that counteracts apoptosis and allows intracellular recycling of macromolecules. Hydroxychloroquine (HCQ) is an autophagy inhibitor. We studied whether HCQ treatment in SMAD4 deficient PDA may prevent therapeutic resistance induced by autophagy upregulation. We retrospectively analyzed the SMAD4 status of patients with PDA enrolled in two prospective clinical trials evaluating pre‐operative HCQ. The first dose escalation trial demonstrated the safety of preoperative gemcitabine with HCQ (NCT01128296). More recently, a randomized trial of gemcitabine/nab‐paclitaxel +/− HCQ evaluated Evans Grade histopathologic response (NCT01978184). The effect of SMAD4 loss on response to HCQ and chemotherapy was studied for association with clinical outcome. Fisher's exact test and log‐rank test were used to assess response and survival. Fifty‐two patients receiving HCQ with neoadjuvant chemotherapy were studied. Twenty‐five patients had SMAD4 loss (48%). 76% of HCQ‐treated patients with SMAD4 loss obtained a histopathologic response greater than or equal to 2A, compared with only 37% with SMAD4 intact ( p = 0.006). Although loss of SMAD4 has been associated with worse outcomes, in the current study, loss of SMAD4 was not associated with a detriment in median overall survival in HCQ‐treated patients (34.43 months in SMAD4 loss vs. 27.27 months in SMAD4 intact, p = 0.18). The addition of HCQ to neoadjuvant chemotherapy in patients with PDA may improve treatment response in those with SMAD4 loss. Further study of the relationship among SMAD4, autophagy, and treatment outcomes in PDA is warranted.